Mixed pine and spruce stands in the Luga-Volkhov and Valdai-Tikhvin landscape districts of the Leningrad Region. Issue 1 (November 2021) - Danilov, D.A.; Yakovlev, A.A.; Bogdanova, L. S.; Boitsov, A.K.; Suvorov, S.A.
Abstract: Pine- and spruce-dominatedmixed stands occupy a substantial part of the forested area. Depending on soil and hydrological conditions of different landscapes, stands of different forest types and tree stand composition dominate. Modern forestry is focused on growing monodominant stands, but it is worth noting that mixed stands have higher productivity and stability. This work is devoted to identifying the patterns of distribution of mixed stands by forest type in different geographic landscapes. For the study, two landscape districts of the Leningrad Region (Valdaysko-Tikhvinsky and Luzhsko-Volkhovsky) with landscape mosaics of different structure were selected. The dominant forest types and types of mixed forest stands were determined by summing the areas of each plant association. To carry out the calculations, data of the state forest inventory of the Leningrad Region were used. In the course of this study, it was found that blueberry forest type was the most common forest type in mixed stands. Most of the landscapes of the study region were dominated by spruce-deciduous stands, but in some landscapes with hilly relief, a predominance of spruce-pine stands was observed.